The social impact and factors influencing the «Phygital football – everyone plays» festival - Glazkova G.B.; Dubrov A.A.; Uvarova N.N.; Nachevskiy M.V. (Theory and Practice of Physical Culture, 2025)
Objective of the study was to scientific and empirical validation of the social impact of phygital football festivals at the local level. Methods and structure of the study. The Kursk region was selected as the pilot location for the implementation of the project «Social and Sports Festival «Phygital Football — Everyone Plays!» (Festival) in 2024. The project was supported by experts from the Plekhanov Russian University of Economics, who provided scientific, methodological, informational, research, and analytical assistance. Results and conclusions. During the execution of the project, the following social impacts were observed: a surge in interest in phygital football among young people, with students continuing to play friendly matches between their departments after the official competitions, thanks to the dissemination of information about the new sport through meetings with university leaders, the involvement of renowned athletes as promoters, and the participation of girls, including international students. The emotional aspect of digital football, the chance to engage in digital sports regardless of geographical location, and the potential for students to participate in regular physical activity and mass sporting events in the face of contemporary social challenges.